Gestión de los procesos de compras públicas aplicados en la Universidad Técnica de Cotopaxi - Gutiérrez Guanoluisa, Mayra Consuelo (2018)
Public purchases in Ecuador are regulated by the Organic Law of the Public National System Procurement approved and published on the Official Gazette Supplement No. 395, on August 4, 2008, which has evolved over the years; characterized to incorporate principles of transparency and non-discrimination; Its objective is to boost national production, promote the participation of small and medium-sized businessmen, guaranteeing transparency and agility in all contracting processes. The objective of this research is to produce a process manual that regulates different acquisitions of goods and services from Technical University of Cotopaxi, for this the process manual proposed by Mr. Jaime Cadena; Director of National Quality Polytechnic School was developed in order to fulfill an adequate planning, organization, direction and control in a company or organization. The methodology of the research is based on a qualitative approach with a exploratory type or investigative research designing, using techniques such as direct observation, and the use of matrices that to allow gather information and their respective description of activities, the same that allows to fulfill an administrative quality management; It should be emphasized that all the requesting units must take into account that when initiating a process, through the application of an interview, the detail of the processes that each officer performs within the unit was obtained in a physical manner, which helped to theoretically support the research variables in order to sustain the proposed project and thereby unify the necessary elements for the preparation of a manual of public procurement processes that allows the optimization of time and resources used in each order, in order to improve the processes and clearly meet each of the requirements that enter the department of the institution. On the other hand, all the requesting units must take into account that when initiating a process they are clearly involved in the purchasing field, which is why they should have a vision and a clear and propitious approach that allows to fully comply with the activities planned for the good of the institution. .